Opportunities and challenges in the application of spatiotemporal transcriptomics in plant research - Deng, Peilei; Huang, Jiaruo; He, Wencan; Li, Zhiyuan; Guo, Cun; Chen, Guoxin; Li, Xiaoxu; Zhong, Kejun; Luo, Wei; Kong, Bo (Frontiers in Plant Science, 2025)
Spatiotemporal heterogeneity is recognized as a key driver of functional diversity in tissues. Spatial transcriptomics, which integrates high-throughput transcriptomics with high-resolution tissue imaging, enables the precise mapping of gene expression patterns at the tissue section level. This technology overcomes the limitations of traditional transcriptomics by providing spatial context and applying unbiased bioinformatics approaches. With the rapid advancement of sequencing technologies, spatial transcriptomics is a pivotal tool for exploring cell fate determination, tissue development, and disease mechanisms, and its underlying principles, technical variations, practical performance, and future directions collectively provide robust theoretical and methodological support for systematically unveiling the spatiotemporal regulation of life processes.